BREAKING THE CYCLE: HOW THROMBOCYTOSIS AMPLIFIES RISKS IN PERIPARTUM CARDIOMYOPATHY WITH SEVERE VALVE DYSFUNCTION: MEMUTUS SIKLUS: BAGAIMANA TROMBOSITOSIS MEMPERBESAR RISIKO PADA KARDIOMIOPATI PERIPARTUM DENGAN DISFUNGSI KATUP BERAT - Sidhi Laksono; Tonni Zheng (Ibnu Sina: Jurnal Kedokteran dan Kesehatan - Fakultas Kedokteran Universitas Islam Sumatera Utara, 2026)
Peripartum cardiomyopathy (PPCM) is a rare but serious condition involving heart failure with reduced ejection fraction developing late in pregnancy or within five months postpartum. Thrombocytosis may increase thromboembolic risk, and severe functional mitral regurgitation (MR) from left-ventricular dilation further worsens clinical status. A 38-year-old woman, three months postpartum, presented with worsening dyspnea, orthopnea, paroxysmal nocturnal dyspnea, and leg edema. She had hypertension and dyslipidemia. Examination revealed fluid overload and elevated jugular venous pressure. ECG showed sinus tachycardia with ST-T changes, and chest X-ray demonstrated cardiomegaly with pulmonary congestion. Laboratory testing identified thrombocytosis (platelets 627,000/µL). Echocardiography revealed severe LV dilation (LVEDD 63 mm), markedly reduced ejection fraction (21%), grade 3 diastolic dysfunction, severe functional MR, and spontaneous echo contrast. This case illustrates the interaction of PPCM, reactive thrombocytosis, and severe MR, emphasizing the need for thorough cardiac–hematologic evaluation and multidisciplinary management to optimize outcomes.